IMPLEMENTASI METODE TEXT MINING DAN METODE ADDIE DALAM PEMBUATAN APLIKASI RPP GENERATOR: IMPLEMENTASI METODE TEXT MINING DAN METODE ADDIE DALAM PEMBUATAN APLIKASI RPP GENERATOR - Khabib, M Umar; Wahyu Puspitarini, Erri; Kurnia Sari, Maydah (Jurnal Sistem Informasi Aplikasi Teknologi Informasi, 2024)
Based on Permendikbud Number 22 of 2016, it is stated that every teacher in an education unit is obliged to prepare a complete and systematic Learning Implementation Plan (RPP). Each teacher is required to compile an integrated RPP. However, not a few teachers have difficulty determining the RPP model that really fits the needs of students. To overcome this problem, create a website based RPP Generator application that can analyze Basic Competency (KD), suggest suitable learning models, and integrate them in RPP format according to applicable regulations. and can be accessed anywhere. The text mining method is used to analyze KD3 - KD4 linearity and recommends a learning model based on Operational Verbs (KKO Revised Bloom's Taxonomy, Dave - Simpson). While the application development model uses the Analysis, Design, Develop, Implement, and Evaluation (ADDIE) development method which is integrated with the prototype development model at the design stage. The results of this study resulted in a website based RPP Generator software which will later be able to assist teachers in compiling lesson plans